2017
DOI: 10.1111/jop.12662
|View full text |Cite
|
Sign up to set email alerts
|

Association between a single‐nucleotide polymorphism in the GREM1 gene and non‐syndromic orofacial cleft in the Chinese population

Abstract: Our findings revealed that the GREM1 polymorphism was significantly associated with the risk of NSOC in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Later this same group confirmed that GREM1 , mainly represented by variant rs1258763, is associated with NSCL±P and provided further evidences showing that Gremlin 1 is expressed in the lip and soft palate during mouse development, and embryonic palatal shelves developed altered shapes when cultured in the presence of recombinant protein (Ludwig et al, ). In concordance, GREM1 rs1258763 was associated with high odds for NSCL±P in populations from Central African and Southeast Asian countries (Figueiredo et al, ) and from China (Wang et al, ). Notably, protective effects of GREM1 variants, represented by rs16969681, rs16969816, rs16969862, and rs1258763, against NSCL±P was reported in the Polish population (Mostowska et al, ).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Later this same group confirmed that GREM1 , mainly represented by variant rs1258763, is associated with NSCL±P and provided further evidences showing that Gremlin 1 is expressed in the lip and soft palate during mouse development, and embryonic palatal shelves developed altered shapes when cultured in the presence of recombinant protein (Ludwig et al, ). In concordance, GREM1 rs1258763 was associated with high odds for NSCL±P in populations from Central African and Southeast Asian countries (Figueiredo et al, ) and from China (Wang et al, ). Notably, protective effects of GREM1 variants, represented by rs16969681, rs16969816, rs16969862, and rs1258763, against NSCL±P was reported in the Polish population (Mostowska et al, ).…”
Section: Introductionmentioning
confidence: 68%
“…Only few genetic studies have been carried out regarding the impact of GREM1 variants on the risk of NSCL±P, and the results varied among different populations (Al Chawa et al, ; Figueiredo et al, ; Gowans et al, ; Ludwig et al, ; Mostowska et al, ; Wang et al, ). Sequencing analysis in Central Europeans identified 33 incompletely penetrant variants in GREM1 , suggesting a putative contribution of GREM1 for NSCL±P (Al Chawa et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GREM-1 binds to BMP2, BMP4, and BMP7 and inhibits BMP signaling. 60 Further validation assays using a luciferase reporter assay confirmed that mechanistically, GREM-1 was the direct target gene of the differentially expressed miRNAs miR-3679-5p and miR-6747-5p (Figure 6). A functional test of GREM-1 suggested that there was an indirect connection between GREM-1 and miR-6515.…”
Section: The Lipid Bilayers Of Exosomes Can Effectively Protect Multiplementioning
confidence: 77%